Review: Shuvinai Ashoona: Mapping Worlds - Megan Macken; Jerrold Shiroma; Terrie Wilson (Art Libraries Society of North America, 2023)
Book review of Shuvinai Ashoona: Mapping Worlds edited by Gaëtane Verna. Hirmer, August 2021. 344 p. ill. ISBN 978-3-7774-3452-0 (h/c), $57.00. https://press.uchicago.edu/ucp/books/book/distributed/S/bo51608339.html. Reviewed January 2023 by Jerrold Shiroma, University Archivist and Librarian for Special Collections, University of California, Merced, jshiroma@ucmerced.edu